Glycated CD59 is a potential biomarker for gestational diabetes mellitus - Wang, Wanying; Xu, Chong; Lu, Xiaofan; Cao, Wei; Zuo, Tengzi; Zhang, Ying; Zou, Huiling; Sun, Yu (Frontiers in Endocrinology, 2024)
Objective: To explore the diagnostic value of glycosylated CD59 (gCD59) in gestational diabetes mellitus (GDM).Methods: A total of 707 pregnant women who underwent the first visit in the obstetric outpatient clinic of Suqian Hospital Affiliated to Xuzhou Medical University from January 2022 to July 2023 were included, and were grouped according to the International Association of the Diabetes and Pregnancy Study Groups(IADPSG) diagnostic criteria, and finally 113 cases in the GDM group and 559 cases in the normal glucose tolerance (NGT) group were included, and the concentration of gCD59 was determined by enzyme-linked immunosorbent assay (ELISA). The baseline data characteristics of the two groups were compared, the risk factors for GDM were explored by multivariate binary logistic analysis, and the diagnostic value of gCD59 in predicting GDM was explored by receiver operating characteristic (ROC) curve analysis.Results: The level of gCD59 in the GDM group was significantly higher than that in the NGT group (1.49 SPU vs 0.87 SPU). Multivariate regression analysis showed that gCD59, diastolic blood pressure(DBP) and thyroid stimulating hormone(TSH) were independent risk factors for GDM.The area under the curve (AUC) of gCD59 for the diagnosis of GDM was 0.681 (95% CI: 0.583-0.717), with a sensitivity of 71.7% and a specificity of 58.3%. In combination with fasting glucose, gCD59 effectively diagnosed GDM with higher AUC of 0.871 (95% CI: 0.708-1.000). Conclusion: gCD59 is an independent risk factor for GDM and a good biomarker for the diagnosis of GDM.